A preparation method of corrosion-resistant composite material and its application in steel doors and windows
By modifying graphene and eloite, the corrosion resistance and mechanical properties of the composite material are improved, and the problem of poor compatibility between graphene and matrix resin in the prior art is solved, and excellent application effect is achieved in steel doors and windows.
Patent Information
- Application Number
- CN202510281876.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the application of existing corrosion-resistant composite materials in steel doors and windows, graphene and matrix resin are poorly compatible, resulting in insufficient corrosion resistance and dispersion.
By modifying graphene and eloite, their dispersion and barrier properties are increased. Modified graphene is grafted by polyvinyl alcohol and citric acid and crosslinked with fluoroisocyanate to form a three-dimensional network structure. Modified Elosite was constructed by sol-gel method and fluorination modification to construct a hydrophobic nanosilicon dioxide micro-nano structure.
It improves the corrosion resistance, hydrophobicity and mechanical properties of composite materials, extends the waterproofness and corrosion resistance of the coating, and enhances the hardness and strength of fluorocarbon coatings.
Smart Images

Figure CN119775829A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a preparation method of a corrosion-resistant composite material and application of the composite material in steel doors and windows. Background Art
[0002] Metal corrosion refers to the interaction between corrosive media such as acids, alkalis, salts and microorganisms in the environment, H2O and O2 molecules in the atmosphere and metal substrates, causing the material to degrade, resulting in performance degradation. Compared with visible disasters such as tsunamis and typhoons, the silent disaster of metal corrosion is a greater problem. Data show that the economic losses caused by all natural disasters in the world each year are far less than those caused by metal corrosion. Moreover, the corrosion of metal containers in industry will cause the leakage of harmful substances such as waste liquids, which will cause environmental damage. In addition, the corrosion of building facilities will also cause accidents and endanger personal safety. Therefore, the problem of metal corrosion has become a major obstacle to industrial progress and environmental green development.
[0003] Corrosion protection technology plays an important role in protecting metal resources and controlling environmental pollution. The main protection measures currently include electrochemical protection such as coatings, electroplating, sacrificial anodes, impressed current cathodic protection, etc. Coating protection is the most effective economical protection method. The coating protection mechanism is mainly to mechanically protect the substrate and isolate the penetration of corrosive media. At present, anti-corrosion coatings mainly include polyurethane, epoxy, acrylic, and fluorocarbon. Fluorocarbon coatings have good weather resistance and anti-corrosion properties and are widely used in material anti-corrosion. However, pure fluorocarbon coating systems have defects such as insufficient anti-fouling and self-cleaning ability, poor barrier properties, and unstable performance.
[0004] Graphene has the advantages of high aspect ratio, impermeability and good mechanical properties. It can be used as a filler to enhance the barrier properties of the coating. However, pure graphene with a perfect six-membered ring system is difficult to disperse in the coating, and large agglomerated graphene cannot exert good barrier properties. Graphene oxide is a derivative of graphene, which greatly improves the dispersibility of graphene. However, due to its rich oxygen-containing functional groups on the surface, including hydroxyl, epoxy and carboxyl groups, it has strong hydrophilicity. When it is used as a filler and composited with the coating, hydrophilic channels are easily formed at the interface to accelerate the water penetration process of the coating. Therefore, it is necessary to modify the graphene oxide to improve the barrier properties while maintaining its dispersibility.
[0005] Prior art, such as Chinese patent application CN110467788A, discloses a corrosion-resistant glass fiber reinforced plastic composite material and a preparation method thereof, comprising the following components in parts by weight: 20-22 parts of glass fiber, 14-20 parts of epoxy resin, 16-20 parts of polytetrafluoroethylene emulsion, 1-2 parts of graphene, 10-12 parts of water-based acrylic resin, 4-6 parts of basalt fiber, 2-4 parts of acetylene black, 3-4 parts of molybdenum dioxide, 1-3 parts of calcium phosphate, 1-1.8 parts of quartz powder, 3-4 parts of coal gangue powder, 1-2 parts of nickel fluoroborate, 2-4 parts of 3,5-dinitro-3,5-diazaheptane, 3-4 parts of plasticizer, 2-3 parts of antioxidant, and 1-2 parts of curing agent. The composite material adds a variety of fiber components to ensure the strength of the product and improve the corrosion resistance of the FRP. However, the graphene is blended with epoxy resin for modification. Due to the poor compatibility of graphene with the matrix resin and poor dispersion in the material, the corrosion resistance of the resulting composite material needs to be improved. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a corrosion-resistant composite material and a preparation method thereof and application in steel doors and windows. The composite material has strong corrosion resistance, hydrophobicity and excellent mechanical properties and can be applied to steel doors and windows.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a corrosion-resistant composite material comprises the following steps: Step (1), preparing modified graphene-based corrosion inhibition material and modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing: S11, mixing graphene oxide and water, ultrasonically dispersing, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, reacting, filtering, washing, and drying after the reaction is completed to obtain the graphene-based corrosion inhibition material; S12, mixing the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF), reacting, filtering, washing, and drying after the reaction is completed to obtain the modified graphene-based corrosion inhibition material; wherein the modified halloysite comprises the following steps of preparing: mixing halloysite, ethanol, and 25wt% ammonia water, ultrasonically dispersing, adding tetraethyl orthosilicate (TEOS), reacting, adding 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continuing the reaction, centrifuging, washing, and drying after the reaction is completed to obtain the modified halloysite; Step (2), mixing high-solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, continuing to stir, obtaining a stirred product, post-treating to obtain component A; mixing component A with component B curing agent IPDI trimer, stirring, and obtaining a high-solid fluorocarbon coating; Step (3), spraying the high solid content fluorocarbon coating on the surface of the base material and curing it to obtain a corrosion-resistant composite material.
[0008] Preferably, in step (1), when preparing the modified graphene-based corrosion inhibition material, in S11: the mass ratio of graphene oxide, water, citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate is (0.05-0.2): (120-160): (2-4): (24-28): (1-2); the reaction conditions are: react at pH = 9-10 and 90-100°C for 20-24h.
[0009] Preferably, in step (1), when preparing the modified graphene-based corrosion inhibition material, in S12: the mass ratio of the graphene-based corrosion inhibition material, the fluorinated isocyanate, and N,N-dimethylformamide (DMF) is 1: (8-10): (50-70); and the reaction conditions are: reacting at a temperature of 85-95° C. for 6-8 hours.
[0010] Preferably, when preparing the modified graphene-based corrosion inhibition material, the fluorinated isocyanate is prepared by the following steps: mixing isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and a catalyst dibutyltin dilaurate, reacting, adding trimethylolpropane after the reaction, continuing the reaction, precipitating, filtering, and drying to obtain the fluorinated isocyanate.
[0011] Furthermore, the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is 1: (1-1.2): (1-1.2); the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate is 10: (80-100): (0.1-0.3); the reaction conditions are: react at a temperature of 40-50°C for 8-10h; the continued reaction conditions are: continue the reaction at a temperature of 80-90°C for 4-6h.
[0012] Preferably, in the step (1), when preparing the modified halloysite, the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), and 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:(36-40):(14-18):(4-6):(0.8-1); the reaction conditions are: reacting at a temperature of 40-60°C for 6-8h; and the continued reaction conditions are: continuing the reaction at a temperature of 40-60°C for 2-3h.
[0013] Preferably, in the step (2), when preparing component A, the mass ratio of high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metallic zinc powder is 50: (1-2): (0.1-0.3): (0.1-0.5): (1-3): (1-3): (0.005-0.02) : (6-10): (6-10): (8-12): (8-12): (20-30): (2-4); stirring conditions: stirring at a speed of 800-1000r / min for 10-20min; continued stirring conditions: continuing stirring at a speed of 1200-1500r / min for 30-40min; post-processing steps include: dispersing on a sand mill to a fineness of 20-30μm, and filtering the stirred product with a 200-mesh copper mesh.
[0014] Preferably, in step (2), when preparing the high-solid fluorocarbon coating, the mass ratio of component A to component B curing agent IPDI trimer is 100:(8-12); and the stirring conditions are: stirring at a speed of 1200-1500 r / min for 30-40 min.
[0015] Preferably, in step (3), when preparing the corrosion-resistant composite material, the spraying conditions are: spraying 2-4 times at 35-55% humidity, 0.2-0.3 MPa pressure, and 10-20°C temperature, with a thickness of 80-160 μm; and the curing conditions are: curing at 200-220°C for 10-15 min.
[0016] Preferably, in step (3), when preparing the corrosion-resistant composite material: the matrix material is a steel material, and the mass percentages of the elements in the steel material are: Sc, Gd, Ce elements: 1-3%, C element: 0.05-0.07%, Mn element: 0.4-0.8%, Si element: 0.21-0.23%, P element: 0.005-0.007%, S element: 0.001-0.003%, Nb element: 0.092-0.094%, V element: 0.05-0.07%, Ti element: 2.5-2.9%, Al element: 1.4-1.6%, N element: 0.001-0.003%, H element: 0.0001-0.00015%, Cu element: 0.04-0.06%, Cr element: 7.2-11.2%, Ni element: 7.5-9.5%, Mo element: 0.22-0.24%, La element: 0.20-0.22%, Sr element: 0.04-0.06%, Th element: 0.04-0.08%, Be element: 0.02-0.025%, Zr element: 0.04-0.06%, B element: 0.0014-0.0018%, Re element: 0.06-0.08%, the balance is Fe and inevitable trace elements.
[0017] Preferably, a corrosion-resistant composite material is prepared by the method for preparing a corrosion-resistant composite material as described above.
[0018] Preferably, a corrosion-resistant composite material prepared by the method for preparing a corrosion-resistant composite material as described above is used in steel doors and windows.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: graphene has high hardness, high strength and excellent wear resistance. Directly adding it to fluorocarbon coatings can improve the hardness, strength and wear resistance of the coatings, and at the same time has an anti-corrosion effect. Since graphene has a special lamellar structure, it can improve and extend the waterproofness, corrosion resistance and service life of the coating by extending the penetration path of water and corrosive media. Graphene can also reduce the microscopic defects and pinholes of the fluorocarbon coating matrix, achieve the purpose of sealing holes, and improve the air tightness and anti-seepage performance of the coating.
[0020] The present invention uses graphene oxide as a filler for functional modification, and grafts polyvinyl alcohol and citric acid onto the surface of graphene oxide in a one-step method, thereby increasing the active sites on the graphene oxide, thereby increasing the loading sites of the green corrosion inhibitor cerium hydroxide, and realizing a large amount of cerium hydroxide loading on the graphene oxide. 2+ or Fe 3+ O2 is reduced to form OH - , and Ce(OH)3 will decompose into Ce3+ and OH - , sufficient OH - With Ce 3+ The combination will further generate a stable insoluble cerium oxide precipitate, thereby blocking the active sites of the cathode and inhibiting the occurrence of corrosion reactions, so that the corrosion inhibitor and graphene oxide produce a synergistic anti-corrosion effect, improving its corrosion resistance, thereby improving the corrosion resistance of the coating; based on the chemical grafting technology, hexafluoroisopropanol, isophorone diisocyanate (IPDI) and trimethylolpropane are used as the main raw materials to synthesize fluorinated isocyanates, which are used as cross-linking agents to cross-link with graphene-based corrosion inhibition materials to obtain modified graphene-based corrosion inhibition materials. By forming a three-dimensional network structure, its dispersibility in fluorocarbon coatings is improved, and by introducing CF bonds on the surface of graphene-based corrosion inhibition materials, its compatibility with fluorocarbon coatings is improved; in addition, the nucleophilic addition reaction of isocyanate groups and hydroxyl groups obtains stable carbamate bonds, which are not easily hydrolyzed or dissolved by strong acids and alkalis, further improving the corrosion resistance of the modified graphene-based corrosion inhibition materials, while eliminating a large number of hydroxyl groups in the graphene-based composite materials and reducing the overall hydrophilicity of the coating.
[0021] The present invention selects hydroxyl-rich halloysite as a filler for functional modification, and utilizes a sol-gel method and fluorination modification to in-situ grow hydrophobic nano-silica on its surface. On the one hand, a micro-nano structure is constructed to improve the hydrophobicity of the halloysite, thereby improving the hydrophobicity of the coating; on the other hand, by introducing CF bonds on the surface of the halloysite, the compatibility of the modified halloysite with the fluorocarbon coating is improved, the interface interaction can be enhanced, and the deformation and cracking of the coating can be inhibited.
[0022] In addition to the above-mentioned modified fillers, the present invention adds fillers such as titanium dioxide and metal zinc powder to the fluorocarbon coating. The addition of titanium dioxide greatly improves the density and adhesion of the coating, can fill the pore defects left by the volatilization of the solvent during the curing process, and can effectively prevent metal corrosion and wear through physical barriers, friction reduction and lubrication, and storage of self-repairing materials, thereby improving the corrosion resistance of the coating; metal zinc powder is a sacrificial anode metal filler, which allows the base material to be cathodically protected, and at the same time, the corrosion products of zinc are attached to the surface of zinc powder and steel materials, so that the shielding effect of the coating is enhanced.
[0023] The present invention adds three kinds of modified elements, Sc, Gd and Ce, to the base material, which can significantly improve the metallographic structure of the base material, refine the grains, reduce the secondary intergranular spacing, reduce harmful gases and impurities in the alloy, and reduce crack sources, thereby further improving the strength and hardness of the steel material and improving the processing performance of the steel material. The high-solid fluorocarbon coating is sprayed on the surface of the base material, and the obtained composite material has strong corrosion resistance, hydrophobicity and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a process flow chart for preparing the corrosion-resistant composite material in the present invention; Figure 2 It is a bar graph of water contact angle of high solid fluorocarbon coating in comprehensive performance test of corrosion-resistant composite materials prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention; Figure 3 It is a bar graph of the water absorption rate of the high solid content fluorocarbon coating in the comprehensive performance test of the corrosion-resistant composite materials prepared by Examples 1-5 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Example 1 This embodiment discloses a method for preparing a corrosion-resistant composite material, comprising the following steps: Step (1), preparing a modified graphene-based corrosion inhibition material and a modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing the material: S11, mixing graphene oxide and water, ultrasonically dispersing for 15 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 20 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 10, reacting at 90°C for 24 hours, filtering after the reaction, taking the precipitate, adding 3 times the mass of the precipitate N,N-dimethylformamide (DMF) to wash 4 times, and drying at 60°C for 6 hours to obtain a graphene-based corrosion inhibition material; wherein, graphene oxide, water, citric acid, The mass ratio of 2wt% polyvinyl alcohol aqueous solution and cerium nitrate is 0.2:160:4:28:2; S12, isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate are mixed, and the reaction is carried out at 50°C for 8 hours. After the reaction is completed, trimethylolpropane is added, and the reaction is continued at 90°C for 4 hours. After the reaction is completed, a reaction product is obtained, and 0°C ice hexane with a volume of 6 times the volume of the reaction product is added for precipitation, and the precipitate is filtered and taken. It is dried at 60°C for 20 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is 1 : 1.2:1.2; the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate is 10:100:0.3; the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF) are mixed in a mass ratio of 1:10:70, and reacted at 85°C for 8 hours. After the reaction is completed, filter, take the precipitate, add dichloromethane 3 times the mass of the precipitate to wash 4 times, and dry at 60°C for 6 hours to obtain a modified graphene-based corrosion inhibition material; wherein the modified halloysite is prepared by the following steps: halloysite, ethanol, and 25wt% ammonia water are mixed, ultrasonically dispersed for 60 minutes, and added Add tetraethyl orthosilicate (TEOS), react at 60°C for 6h, add 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continue to react at 60°C for 3h, centrifuge at 5000r / min for 15min after the reaction, take the precipitate, add ethanol and water 3 times the mass of the precipitate respectively, wash 4 times, dry at 80°C for 8h, and obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), and 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:40:18:6:1; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 1000 r / min for 10 minutes, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1500 r / min for 30 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 20 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein the high solid The mass ratio of FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide and metal zinc powder is 50:2:0.3:0.5:3:3:0.02:10:10:12:12:30:4; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:12, and stirred at a speed of 1500r / min for 30min to obtain a high-solid fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 220° C. for 10 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying 4 times at a humidity of 35%, a pressure of 0.3 MPa, and a temperature of 20° C., and the thickness is 160 μm; the base material is a steel material, and the mass percentages of the elements in the steel material are: Sc, Gd, Ce elements: 3%, C element: 0.07%, Mn element: 0.8%, Si element: 0.23%, P element: 0.007%, S element: 0.003%, Nb element: 0.094%, V element: 0.07%, Ti element: 2.9%, Al element: 1.6%, N element: 0.003%, H element: 0.00015%, Cu element: 0.06%, Cr element: 11.2%, Ni element: 9.5%, Mo element: 0.24%, La element: 0.22%, Sr element: 0.04-0.06%, Th element: 0.08%, Be element: 0.025%, Zr element: 0.06%, B element: 0.0018%, Re element: 0.08%, and the balance is Fe and inevitable trace elements.
[0027] Example 2 Step (1), preparing a modified graphene-based corrosion inhibition material and modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing: S11, mixing graphene oxide and water, ultrasonically dispersing for 10 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 10 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 9, reacting at 100°C for 20 hours, after the reaction is completed, filtering, taking the precipitate, adding 5 times the mass of the precipitate N,N-dimethylformamide (DMF) to wash twice, and drying at 50°C for 8 hours to obtain a graphene-based corrosion inhibition material; wherein, graphene oxide, water, citric acid, The mass ratio of 2wt% polyvinyl alcohol aqueous solution and cerium nitrate is 0.05:120:2:24:1; S12, isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate are mixed, and the reaction is carried out at 40°C for 10 hours. After the reaction is completed, trimethylolpropane is added, and the reaction is continued at 80°C for 6 hours. After the reaction is completed, a reaction product is obtained, and 0°C ice hexane with a volume of 4 times the volume of the reaction product is added for precipitation, and the precipitate is filtered and dried at 50°C for 24 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is The mass ratio of isophorone diisocyanate (IPDI), ethyl acetate and catalyst dibutyltin dilaurate is 10:80:0.1; the graphene-based corrosion inhibition material, fluorinated isocyanate and N,N-dimethylformamide (DMF) are mixed in a mass ratio of 1:8:50, reacted at 95°C for 6 hours, filtered after the reaction, the precipitate is taken, and dichloromethane 5 times the mass of the precipitate is added to wash twice, and dried at 50°C for 8 hours to obtain a modified graphene-based corrosion inhibition material; wherein the modified halloysite is prepared by the following steps: halloysite, ethanol and 25wt% ammonia water are mixed, ultrasonically dispersed for 40 minutes, and orthosilicic acid is added Ethyl orthosilicate (TEOS), react at 40°C for 8h, after the reaction, add 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continue to react at 40°C for 2h, after the reaction, centrifuge at 6000r / min for 10min, take the precipitate, add 5 times the mass of ethanol and water to wash twice, dry at 60°C for 12h, and obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:36:14:4:0.8; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 800 r / min for 20 minutes, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1200 r / min for 40 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 30 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein, ... The mass ratio of solid content FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metal zinc powder is 50:1:0.1:0.1:1:1:0.005:6:6:8:8:20:2; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:8, and stirred at a speed of 1200r / min for 40min to obtain a high-solid content fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 200° C. for 15 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying twice at a humidity of 55%, a pressure of 0.2 MPa, and a temperature of 10° C., with a thickness of 80 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0028] Example 3 This embodiment discloses a method for preparing a corrosion-resistant composite material, comprising the following steps: Step (1), preparing a modified graphene-based corrosion inhibition material and a modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing the material: S11, mixing graphene oxide and water, ultrasonically dispersing for 14 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 18 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 10, reacting at 92°C for 23 hours, after the reaction is completed, filtering, taking the precipitate, adding 3 times the mass of the precipitate N,N-dimethylformamide (DMF) to wash 4 times, and drying at 58°C for 6 hours to obtain a graphene-based corrosion inhibition material; wherein, graphene oxide, water, citric acid, 2 The mass ratio of wt% polyvinyl alcohol aqueous solution and cerium nitrate is 0.16:150:3.5:27:2; S12, isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate are mixed, and the reaction is carried out at 48°C for 8 hours. After the reaction is completed, trimethylolpropane is added, and the reaction is continued at 88°C for 4 hours. After the reaction is completed, a reaction product is obtained, and 0°C ice hexane with a volume of 6 times that of the reaction product is added for precipitation, and the precipitate is filtered, and the precipitate is taken and dried at 58°C for 21 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is 1 : 1.2:1.2; the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate is 10:95:0.3; the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF) are mixed in a mass ratio of 1:9.5:65, and reacted at 88°C for 8 hours. After the reaction is completed, filter, take the precipitate, add dichloromethane 3 times the mass of the precipitate to wash 4 times, and dry at 58°C for 6 hours to obtain a modified graphene-based corrosion inhibition material; wherein the modified halloysite is prepared by the following steps: halloysite, ethanol, and 25wt% ammonia water are mixed, ultrasonically dispersed for 55 minutes, and added Tetraethyl orthosilicate (TEOS) was reacted at 55°C for 6 hours. After the reaction, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane (FAS) was added and the reaction was continued at 55°C for 3 hours. After the reaction, the mixture was centrifuged at 5200 r / min for 14 minutes. The precipitate was taken and washed 4 times with ethanol and water in an amount of 3 times the mass of the precipitate, respectively. The mixture was dried at 75°C for 9 hours to obtain modified halloysite. The mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS) and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane (FAS) was 1:39:17:5.5:1. Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 950 r / min for 12 minutes, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1400 r / min for 32 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 22 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein the high solid FE The mass ratio of VE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metal zinc powder is 50:2:0.25:0.4:2.5:2.5:0.016:9:9:11:11:28:3.5; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:11, and stirred at a speed of 1400r / min for 32min to obtain a high-solid fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 215° C. for 12 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying 4 times at a humidity of 40%, a pressure of 0.3 MPa, and a temperature of 18° C., and the thickness is 160 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0029] Example 4 This embodiment discloses a method for preparing a corrosion-resistant composite material, comprising the following steps: Step (1), preparing a modified graphene-based corrosion inhibition material and a modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing the material: S11, mixing graphene oxide and water, ultrasonically dispersing for 13 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 15 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 10, reacting at 95°C for 22 hours, filtering after the reaction, taking the precipitate, adding N,N-dimethylformamide (DMF) 4 times the mass of the precipitate to wash 3 times, and drying at 55°C for 7 hours to obtain a graphene-based corrosion inhibition material; wherein the graphene oxide, water, citric acid, 2 The mass ratio of wt% polyvinyl alcohol aqueous solution and cerium nitrate is 0.12:140:3:26:1.5; S12, isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate are mixed, and the reaction is carried out at 45°C for 9 hours. After the reaction is completed, trimethylolpropane is added, and the reaction is continued at 85°C for 5 hours. After the reaction is completed, a reaction product is obtained, and 0°C ice hexane with a volume of 5 times that of the reaction product is added for precipitation, and the precipitate is filtered, and the precipitate is taken and dried at 55°C for 22 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is 1 : 1.1:1.1; the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate is 10:90:0.2; the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF) are mixed in a mass ratio of 1:9:60, and reacted at 90°C for 7 hours. After the reaction is completed, filter, take the precipitate, add dichloromethane 4 times the mass of the precipitate to wash 3 times, and dry at 55°C for 7 hours to obtain a modified graphene-based corrosion inhibition material; wherein the modified halloysite is prepared by the following steps: halloysite, ethanol, and 25wt% ammonia water are mixed, ultrasonically dispersed for 50 minutes, and orthosilicic acid is added. Ethyl orthosilicate (TEOS), react at 50°C for 7h, after the reaction, add 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continue to react at 50°C for 2.5h, after the reaction, centrifuge at 5500r / min for 13min, take the precipitate, add 4 times the mass of ethanol and water to wash 3 times, dry at 70°C for 10h, and obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:38:16:5:0.9; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 900 r / min for 15 minutes, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1350 r / min for 35 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 25 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein the high solid content The mass ratio of FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metal zinc powder is 50:1.5:0.2:0.3:2:2:0.012:8:8:10:10:25:3; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:10, and stirred at a speed of 1350r / min for 35min to obtain a high-solid fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 210° C. for 13 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying 3 times at a humidity of 45%, a pressure of 0.3 MPa, and a temperature of 15° C., and the thickness is 120 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0030] Example 5 This embodiment discloses a method for preparing a corrosion-resistant composite material, comprising the following steps: Step (1), preparing a modified graphene-based corrosion inhibition material and a modified halloysite; wherein the modified graphene-based corrosion inhibition material comprises the following steps of preparing the material: S11, mixing graphene oxide and water, ultrasonically dispersing for 12 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 12 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 9, reacting at 98°C for 21 hours, filtering after the reaction, taking the precipitate, adding 5 times the mass of the precipitate N,N-dimethylformamide (DMF) to wash twice, and drying at 52°C for 8 hours to obtain a graphene-based corrosion inhibition material; wherein, graphene oxide, water, citric acid, 2w The mass ratio of t% polyvinyl alcohol aqueous solution and cerium nitrate is 0.08:130:2.5:25:1; S12, isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate are mixed, and the reaction is carried out at 42°C for 10 hours. After the reaction is completed, trimethylolpropane is added, and the reaction is continued at 82°C for 6 hours. After the reaction is completed, a reaction product is obtained, and 0°C ice hexane with a volume of 4 times the volume of the reaction product is added for precipitation, and the precipitate is filtered and dried at 52°C for 23 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane is 1:1:1; the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate is 10:85:0.1; the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF) are mixed in a mass ratio of 1:8.5:55, reacted at 92°C for 6 hours, filtered after the reaction, the precipitate is taken, and dichloromethane 5 times the mass of the precipitate is added to wash twice, and dried at 52°C for 8 hours to obtain a modified graphene-based corrosion inhibition material; wherein the modified halloysite is prepared by the following steps: halloysite, ethanol, and 25wt% ammonia water are mixed, ultrasonically dispersed for 45 minutes, and orthosilicic acid is added. Ethyl orthosilicate (TEOS), react at 45°C for 8h, after the reaction, add 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continue to react at 45°C for 2h, after the reaction, centrifuge at 5800r / min for 12min, take the precipitate, add 5 times the mass of ethanol and water to wash twice, dry at 65°C for 11h, and obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:37:15:4.5:0.8; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 850 r / min for 18 minutes, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1300 r / min for 38 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 28 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein the high solid F The mass ratio of EVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metal zinc powder is 50:1:0.15:0.2:1.5:1.5:0.008:7:7:9:9:22:2.5; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:9, and stirred at a speed of 1300r / min for 38min to obtain a high-solid fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 205° C. for 14 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying twice at a humidity of 50%, a pressure of 0.2 MPa, and a temperature of 12° C., with a thickness of 80 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0031] Comparative Example 1 Step (1), preparing modified halloysite; mixing halloysite, ethanol and 25wt% ammonia water, ultrasonically dispersing for 40min, adding tetraethyl orthosilicate (TEOS), reacting at 40°C for 8h, adding 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continuing to react at 40°C for 2h, centrifuging at 6000r / min for 10min after the reaction, taking the precipitate, adding 5 times the mass of ethanol and water respectively, washing twice, and drying at 60°C for 12h to obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), and 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:36:14:4:0.8; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 800 r / min for 20 minutes, adding graphene oxide, modified halloysite, titanium dioxide, and metallic zinc powder, and continuing to stir at a speed of 1200 r / min for 40 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 30 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein, ... The mass ratio of solid content FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, graphene oxide, modified halloysite, titanium dioxide, and metal zinc powder is 50:1:0.1:0.1:1:1:0.005:6:6:8:8:20:2; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:8, and stirred at a speed of 1200r / min for 40min to obtain a high-solid content fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 200° C. for 15 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying twice at a humidity of 55%, a pressure of 0.2 MPa, and a temperature of 10° C., with a thickness of 80 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0032] Comparative Example 2 Step (1), preparing a graphene-based corrosion inhibition material and modified halloysite; wherein the graphene-based corrosion inhibition material is prepared by the following steps: mixing graphene oxide and water, ultrasonically dispersing for 10 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 10 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 9, reacting at 100°C for 20 hours, filtering after the reaction, taking the precipitate, adding 5 times the mass of N,N-dimethylformamide (DMF) of the precipitate to wash twice, and drying at 50°C for 8 hours to obtain a graphene-based corrosion inhibition material; wherein the mass ratio of graphene oxide, water, citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate is 0.05:120:2:24:1; wherein the modified halloysite comprises the following The method is prepared by the following steps: mixing halloysite, ethanol and 25wt% ammonia water, ultrasonically dispersing for 40 minutes, adding tetraethyl orthosilicate (TEOS), reacting at 40°C for 8 hours, adding 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS), continuing to react at 40°C for 2 hours, centrifuging at 6000r / min for 10 minutes after the reaction, taking the precipitate, adding ethanol and water with a mass of 5 times that of the precipitate respectively for washing twice, and drying at 60°C for 12 hours to obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate (TEOS), and 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is 1:36:14:4:0.8; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 800 r / min for 20 minutes, adding graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metallic zinc powder, and continuing to stir at a speed of 1200 r / min for 40 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 30 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein, ... The mass ratio of solid content FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metal zinc powder is 50:1:0.1:0.1:1:1:0.005:6:6:8:8:20:2; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:8, and stirred at a speed of 1200r / min for 40min to obtain a high-solid content fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 200° C. for 15 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying twice at a humidity of 55%, a pressure of 0.2 MPa, and a temperature of 10° C., with a thickness of 80 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0033] Comparative Example 3 Step (1), preparing a modified graphene-based corrosion inhibition material; S11, mixing graphene oxide and water, ultrasonically dispersing for 10 minutes, adding citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate, stirring for 10 minutes, adding 20wt% NaOH aqueous solution to adjust the pH to 9, reacting at 100°C for 20 hours, filtering after the reaction, taking the precipitate, adding 5 times the mass of N,N-dimethylformamide (DMF) of the precipitate to wash twice, and drying at 50°C for 8 hours to obtain a graphene-based corrosion inhibition material; wherein the mass ratio of graphene oxide, water, citric acid, 2wt% polyvinyl alcohol aqueous solution, and cerium nitrate is 0.05:120:2:24:1; S12, mixing isophorone diisocyanate (IPDI), hexafluoroisopropanol, ethyl acetate, and catalyst dibutyltin dilaurate, reacting at 40°C for 10 hours, and the reaction is completed. After that, trimethylolpropane was added, and the reaction was continued at 80°C for 6 hours. After the reaction was completed, a reaction product was obtained, and 0°C ice hexane 4 times the volume of the reaction product was added for precipitation, filtered, and the precipitate was taken and dried at 50°C for 24 hours to obtain a fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate (IPDI), hexafluoroisopropanol, and trimethylolpropane was 1:1:1; the mass ratio of isophorone diisocyanate (IPDI), ethyl acetate, and catalyst dibutyltin dilaurate was 10:80:0.1; the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide (DMF) were mixed in a mass ratio of 1:8:50, reacted at 95°C for 6 hours, filtered, and the precipitate was taken, washed twice with dichloromethane 5 times the mass of the precipitate, and dried at 50°C for 8 hours to obtain a modified graphene-based corrosion inhibition material; Step (2), mixing high solid FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring at a speed of 800 r / min for 20 minutes, adding modified graphene-based corrosion inhibition material, halloysite, titanium dioxide, and metal zinc powder, and continuing to stir at a speed of 1200 r / min for 40 minutes to obtain a stirred product, dispersing it on a sand mill to a fineness of 30 μm, and filtering the stirred product with a 200-mesh copper mesh to obtain component A; wherein, ... The mass ratio of solid content FEVE fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, halloysite, titanium dioxide, and metal zinc powder is 50:1:0.1:0.1:1:1:0.005:6:6:8:8:20:2; component A and component B curing agent IPDI trimer are mixed in a mass ratio of 100:8, and stirred at a speed of 1200r / min for 40min to obtain a high-solid content fluorocarbon coating; Step (3), spraying a high-solid fluorocarbon coating on the surface of the base material, and curing it at a temperature of 200° C. for 15 minutes to obtain a corrosion-resistant composite material; wherein the spraying conditions are: spraying twice at a humidity of 55%, a pressure of 0.2 MPa, and a temperature of 10° C., with a thickness of 80 μm; the base material is a steel material, and the mass percentage of the elements in the steel material is the same as that in Example 1.
[0034] In the above embodiments and comparative examples: the steel material is a self-made material, which is prepared by the following steps: steelmaking, continuous casting, rolling, quenching and tempering, annealing, and hot forming; graphene oxide is from Suzhou Kaifa New Material Technology Co., Ltd., model: BK2020062217, CAS No.: 1034343-98-0; citric acid is from Tianjin Dongli Tianda Chemical Reagent Factory, CAS No.: 77-92-9; polyvinyl alcohol is from Tianjin Guangfu Fine Chemical Research Institute, CAS No.: 9002-89-5; cerium nitrate is from Tianjin Komiou Chemical Reagent Co., Ltd., CAS No.: 10294-41-4; isophorone diisocyanate (IPDI) is from Shanghai McLean Biochemical Technology Co., Ltd., CAS No.: 4098-71-9; hexafluoroisopropanol is from Aladdin Biochemical Technology Co., Ltd., CAS No.: 920-66-1; ethyl acetate is from Shanghai Organic Pharmaceutical Chemistry Production Co., Ltd., CAS No.: 141-78-6; dibutyltin dilaurate is from Shanghai Organic Pharmaceutical Chemistry Production Co., Ltd., CAS No.: 77-58-7; trimethylolpropane is from Aladdin Biochemical Technology Co., Ltd., CAS No.: 77- 99-6; N,N-dimethylformamide (DMF) was from Tianjin Tianxin Fine Chemical Development Center, CAS No.: 68-12-2; dichloromethane was from Daliang Town Industrial Park, Wuqing District, Tianjin, CAS No.: 75-09-2; halloysite was from Lingshou Tuyun Mineral Products Processing Plant, model: TY-002; ethanol was from Tianjin Yuanli Chemical Co., Ltd., CAS No.: 64-17-5; ammonia water (25%) was from Tianjin Chemical Reagent Factory, CAS No.: 1336-21-6; tetraethyl orthosilicate (TEOS) was from Tianjin Chemical Reagent Factory, CAS No.: 7 8-10-4; 1H,1H,2H,2H-perfluorodecyltriethoxysilane (FAS) is from Nanjing Quanxi Chemical Co., Ltd., CAS No.: 101947-16-4; high solid FEVE fluorocarbon resin is from Shanghai Fengguang Plastic Technology Co., Ltd., model: GK570; dispersant is from German BYK Chemical Company, model: BYK-P104S; leveling agent is from German BYK Chemical Company, model: BYK-306; defoamer is from German BYK Chemical Company, model: BYK-141; light stabilizer is from BASF, model: Tinuvin 249; light absorber comes from BASF, model: Tinuvin 400; xylene comes from Jiangsu Hualun Chemical; butyl acetate comes from Jiangsu Hualun Chemical, CAS number: 123-86-4; titanium dioxide comes from Chemours Chemical (Shanghai) Co., Ltd., model: R960; metallic zinc powder comes from Shanghai Guanjin Powder Materials Co., Ltd., specification: 800 mesh, CAS number: 7440-66-6; curing agent IPDI trimer comes from Guangzhou Jiuying Chemical Materials Co., Ltd., model: DesmodurBL 4265 SN.
[0035] Test example
[0036] (1) Comprehensive performance test
[0037] The high solid fluorocarbon coatings in the corrosion-resistant composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to comprehensive performance tests, and the specific test results are shown in Tables 1 and 2; the base materials in the corrosion-resistant composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to comprehensive performance tests, and the specific test results are shown in Table 3:
[0038]
[0039]
[0040] The tests of various indicators in the table are based on the following standards: hardness is measured by GB / T 6739-1996 "Pencil test method for coating hardness"; water contact angle is measured by GB / T 30693-2014 "Measurement of contact angle between plastic film and water"; water absorption is measured by GB / T1733-93 "Determination of water resistance of paint film"; salt spray resistance is measured by GB / T1771-2007 "Determination of neutral salt spray resistance of paint and varnish"; acid resistance and alkali resistance are measured by GB / T1763-1979 "Determination of chemical resistance of paint film", and the composite materials are placed in 50g / L H2SO4 aqueous solution and 50g / L NaOH aqueous solution for 168h respectively, and the observations are recorded; tensile strength and yield strength are measured by GB / T228.1-2010 "Room temperature tensile test method for metal materials".
[0041] It can be seen from the test results of Tables 1 and 2 that the high-solid fluorocarbon coating in the corrosion-resistant composite material prepared by the present invention has strong corrosion resistance, hydrophobicity and excellent mechanical properties; it can be seen from the test results of Table 3 that the matrix material in the corrosion-resistant composite material prepared by the present invention has high strength and hardness.
[0042] In Comparative Example 1, the corrosion inhibitor cerium hydroxide is not loaded on graphene oxide, and graphene oxide is directly added as a filler to the fluorocarbon coating. Due to the lack of cerium ions to hinder the corrosion reaction at the defects, the corrosion resistance of the graphene filler is reduced. Since there are hydrophilic groups on the surface of graphene oxide, including hydroxyl, epoxy and carboxyl groups, the water resistance of the fluorocarbon coating is reduced. Therefore, the water contact angle of Comparative Example 1 is smaller than that of the embodiment, the water absorption rate is higher than that of the embodiment, and the salt spray resistance and acid-base resistance are worse than those of the embodiment.
[0043] In Comparative Example 2, the graphene-based corrosion inhibition material is not cross-linked with the fluorinated isocyanate and does not form a three-dimensional network structure, resulting in a decrease in its dispersibility in the fluorocarbon coating. In addition, since no CF bonds are introduced on the graphene surface, its surface energy is increased, which reduces its water resistance and reduces its compatibility with the fluorocarbon coating, thereby affecting the corrosion resistance and hydrophobicity of the fluorocarbon coating. Therefore, the water contact angle of Comparative Example 1 is smaller than that of the embodiment, the water absorption rate is higher than that of the embodiment, and the salt spray resistance and acid-base resistance are worse than those of the embodiment.
[0044] In Comparative Example 3, the halloysite was not hydrophobically and fluorinated, but was directly added to the fluorocarbon coating as a filler. Due to the lack of hydrophobic silica on its surface, the micro-nano rough structure could not be constructed, resulting in a decrease in its hydrophobic performance. At the same time, due to the lack of the reinforcing effect of silica on the matrix material, its mechanical properties were reduced. Since no CF bonds were introduced on the surface of the halloysite, its compatibility with the fluorocarbon coating was reduced. Therefore, the hardness of Comparative Example 1 is worse than that of the embodiment, the water contact angle is smaller than that of the embodiment, and the water absorption rate is higher than that of the embodiment.
[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a corrosion-resistant composite material, characterized in that: The following steps are involved: Step (1), mixing graphene oxide and water, adding citric acid, polyvinyl alcohol aqueous solution, and cerium nitrate, reacting, and purifying after the reaction to obtain a graphene-based corrosion inhibition material; mixing the graphene-based corrosion inhibition material, fluorinated isocyanate, and N,N-dimethylformamide, reacting, and purifying after the reaction to obtain a modified graphene-based corrosion inhibition material; Step (2), mixing fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, and butyl acetate, stirring, adding modified graphene-based corrosion inhibition material, modified halloysite, titanium dioxide, and metallic zinc powder, continuing to stir, post-treating, and obtaining component A; mixing component A with component B curing agent IPDI trimer, stirring, and obtaining a high-solid fluorocarbon coating; Step (3), spraying the high solid content fluorocarbon coating on the surface of the base material and curing it to obtain a corrosion-resistant composite material.
2. The method for preparing a corrosion-resistant composite material according to claim 1, characterized in that: In the step (1), the mass ratio of graphene oxide, water, citric acid, polyvinyl alcohol aqueous solution and cerium nitrate is (0.05-0.2): (120-160): (2-4): (24-28): (1-2), and the concentration of the polyvinyl alcohol aqueous solution is 2wt%. When preparing the graphene-based corrosion inhibition material, the reaction conditions are: reacting at pH = 9-10 and 90-100°C for 20-24h.
3. The method for preparing a corrosion-resistant composite material according to claim 1, characterized in that: In the step (1), the mass ratio of the graphene-based corrosion inhibition material, the fluorinated isocyanate, and the N,N-dimethylformamide is 1: (8-10): (50-70); when preparing the modified graphene-based corrosion inhibition material, the reaction conditions are: reacting at a temperature of 85-95° C. for 6-8 hours.
4. The method for preparing a corrosion-resistant composite material according to claim 3, characterized in that: The fluorinated isocyanate in step (1) is prepared by the following steps: mixing isophorone diisocyanate, hexafluoroisopropanol, ethyl acetate and a catalyst dibutyltin dilaurate, reacting, adding trimethylolpropane after the reaction, continuing the reaction, precipitating, filtering and drying to obtain the fluorinated isocyanate; wherein the molar ratio of isophorone diisocyanate, hexafluoroisopropanol and trimethylolpropane is 1:(1-1.2):(1-1.2); the mass ratio of isophorone diisocyanate, ethyl acetate and a catalyst dibutyltin dilaurate is 10:(80-100):(0.1-0.3); the reaction conditions are: reacting at a temperature of 40-50°C for 8-10 hours; and the continued reaction conditions are: continuing the reaction at a temperature of 80-90°C for 4-6 hours.
5. The method for preparing a corrosion-resistant composite material according to claim 1, characterized in that: In the step (2), the mass ratio of fluorocarbon resin, dispersant, leveling agent, defoamer, light stabilizer, light absorber, dibutyltin dilaurate, xylene, butyl acetate, modified graphene-based corrosion inhibitor, modified halloysite, titanium dioxide, and metallic zinc powder is 50: (1-2): (0.1-0.3): (0.1-0.5): (1-3): (1-3): (0.005-0.02): (6-10): (6-10): (8-12): (8-12): (20-30): (2-4); when preparing component A, the stirring condition is: stirring at a speed of 800-1000 r / min for 10-20 min; the continued stirring condition is: continuing to stir at a speed of 1200-1500 r / min for 30-40 min.
6. The method for preparing a corrosion-resistant composite material according to claim 5, characterized in that: The modified halloysite in step (2) is prepared by the following steps: mixing halloysite, ethanol and 25wt% ammonia water, ultrasonically dispersing, adding tetraethyl orthosilicate, reacting, adding 1H,1H,2H,2H-perfluorodecyltriethoxysilane after the reaction, continuing the reaction, centrifuging, washing and drying to obtain modified halloysite; wherein the mass ratio of halloysite, ethanol, 25wt% ammonia water, tetraethyl orthosilicate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is 1:(36-40):(14-18):(4-6):(0.8-1); the reaction conditions are: reacting at a temperature of 40-60°C for 6-8h; and the continued reaction conditions are: continuing the reaction at a temperature of 40-60°C for 2-3h.
7. The method for preparing a corrosion-resistant composite material according to claim 1, characterized in that: In the step (2), the mass ratio of component A to component B curing agent IPDI trimer is 100:(8-12); when preparing the high-solid fluorocarbon coating, the stirring condition is: stirring at a speed of 1200-1500 r / min for 30-40 minutes.
8. The method for preparing a corrosion-resistant composite material according to claim 1, characterized in that: In the step (3), the spraying conditions are: spraying 2-4 times at 35-55% humidity, 0.2-0.3MPa pressure, 10-20°C temperature, and a thickness of 80-160μm; the curing conditions are: curing at 200-220°C for 10-15min; the base material is a steel material, and the mass percentage of the elements in the steel material is: Sc, Gd, Ce elements: 1-3%, C element: 0.05-0.07%, Mn element: 0.4-0.8%, Si element: 0.21-0.23%, P element: 0.005-0.007%, S element: 0.001-0.003%, Nb element: 0.092-0.094%, V element: 0.05-0.07%, Ti element: 2.5-2.9%, Al element: 1.4-1.6%, N element: 0.001-0.003%, H element: 0.0001-0.00015%, Cu element: 0.04-0.06%, Cr element: 7.2-11.2%, Ni element: 7.5-9.5%, Mo element: 0.22-0.24%, La element: 0.20-0.22%, Sr element: 0.04-0.06%, Th element: 0.04-0.08%, Be element: 0.02-0.025%, Zr element: 0.04-0.06%, B element: 0.0014-0.0018%, Re element: 0.06-0.08%, the balance is Fe and inevitable trace elements.
9. A corrosion-resistant composite material prepared by the method for preparing a corrosion-resistant composite material according to any one of claims 1 to 8.
10. Use of a corrosion-resistant composite material prepared by the method for preparing a corrosion-resistant composite material according to any one of claims 1 to 9 in steel doors and windows.
Citation Information
Patent Citations
Corrosion-resistant glass fiber reinforced plastic composite material, and preparation method thereof
CN110467788A
Novel nano TiO2 / PTFE hybrid fluorocarbon paint applied for resisting pollution flashover of insulators, and preparation method thereof
CN103224741A
Stainless steel material for doors and windows
CN107058876A
Super-weather-resistant graphene modified fluorocarbon coating and preparation method thereof
CN109666347A
Fluorine-containing compound for aqueous resin and preparation and application thereof
CN109929090A